Association between X‐ray repair cross‐complementing group 1 Arg399Gln polymorphism and male infertility: An update meta‐analysis. (14th June 2020) - Lv, Mo‐qi; Li, Yi‐xin; Ge, Pan; Yang, Yan‐qi; Zhang, Jian; Han, Shui‐ping; Zhou, Dang‐xia
Abstract: Numerous studies concentrate on the association between X‐ray repair cross‐complementing group 1 (XRCC1) gene polymorphism and male infertility; however, the results remain inconclusive and inconsistent. Hence, this meta‐analysis was conducted to get a precise estimation of the correlation. PubMed, Web of Science, Embase, Scopus and China National Knowledge Infrastructure (CNKI) databases were searched to identify the all relevant studies before 3 May 2020. Summary odds ratios (ORs) and 95% confidence intervals (95% CIs) were used to assess the strength of the association. Finally, six studies with 1, 886 cases and 1, 212 controls were included in our study. The result indicated that XRCC1 Arg399Gln polymorphism was significantly associated with male infertility under allelic model (A‐allele vs. G‐allele: OR = 1.183, p = .003), heterozygote genetic model (AA vs. GA: OR = 1.256, p = .027), recessive genetic model (AA vs. GG + GA: OR = 1.279, p = .012) and dominant genetic model (AA + GA vs. GG: OR = 1.218, p = .026). In addition, in Asian subgroup, statistic correlation remained significant in allelic model (A‐allele vs. G‐allele: OR = 1.145, p = .025) with rare heterogeneity ( I 2 = 0%). In summary, our meta‐analysis suggested that XRCC1 Arg399Gln polymorphism was significantly associated with male infertility and the A‐allele might be a risk factor for this disease, especially in Asians.